Correlation Analysis on the Performance of Freshmen Students in College Algebra - Estorico, Maricel P. and Sibugan, Ma. Margarette L. 4 0 16; 5
u
Undergraduate Thesis (BS in Mathematics) - Pamantasan ng Lungsod ng Maynila. 2010.
Keywords: 2 -- 0; 6; 20; 20; 2